2015
DOI: 10.1128/jb.00332-15
|View full text |Cite
|
Sign up to set email alerts
|

Homologues of Genetic Transformation DNA Import Genes Are Required for Rhodobacter capsulatus Gene Transfer Agent Recipient Capability Regulated by the Response Regulator CtrA

Abstract: Gene transfer agents (GTAs) morphologically resemble small, double-stranded DNA (dsDNA) bacteriophages; however, their only known role is to package and transfer random pieces of the producing cell genome to recipient cells. The best understood GTA is that of Rhodobacter capsulatus, termed RcGTA. We discovered that homologues of three genes involved in natural transformation in other bacteria, comEC, comF, and comM, are essential for RcGTA-mediated gene acquisition. This paper gives genetic and biochemical evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 63 publications
0
52
0
Order By: Relevance
“…This is especially complicated when evaluating the RcGTA production and recipient capability systems that are regulated by the CckAChpT-CtrA phosphorelay, because CckA may have opposing activities, depending on the magnitude of expression. Furthermore, our results showed that dprA is not differentially expressed in the ⌬lexA mutant, and because competence genes are coregulated with dprA, they are likely not differentially expressed (6,7).…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…This is especially complicated when evaluating the RcGTA production and recipient capability systems that are regulated by the CckAChpT-CtrA phosphorelay, because CckA may have opposing activities, depending on the magnitude of expression. Furthermore, our results showed that dprA is not differentially expressed in the ⌬lexA mutant, and because competence genes are coregulated with dprA, they are likely not differentially expressed (6,7).…”
Section: Discussionmentioning
confidence: 80%
“…LexA appears to directly repress the expression of the histidine kinase homolog CckA, which is involved in the CckA-ChpT-CtrA phosphorelay that regulates several aspects of RcGTA biology, including production, recipient capability, particle maturation, and particle release (4,6,7,12). Because an SOS box is present in the promoter sequence of cckA in environmental isolates B6, YW1, and YW2 (data not shown), whose genomes have been sequenced, in addition to strain SB1003, repression of cckA by LexA appears to be conserved in all strains of R. capsulatus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations